PERAN EVENT BUDAYA OGOH-OGOH DALAM MEMPERKENALKAN BUDAYA ASLI BALI KEPADA WISATAWAN LOKAL - Eva Tabitha Aurelia Iskandar; Dewanta Facrureza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bali's cultural tourism continues to demonstrate significant growth, as reflected in the surge of domestic tourist visits, which reached 26,615,306 trips in 2025, representing a 17.53% increase compared to the previous year. This trend continued with a 42.10% growth in national tourism trips in March 2026. Amid this dynamic development, the ogoh-ogoh cultural event, organized as part of the Nyepi Day celebration, has emerged as one of the most strategic cultural attractions in Denpasar City. However, its potential as an educational medium for domestic tourists has not yet been systematically optimized. This study employed a descriptive qualitative approach using in-depth interviews, direct observation, and documentation involving six informants, namely the Traditional Village Head, Village Secretary, members of the Sekaa Taruna youth organization, a Pecalang officer, and two domestic tourists. Data were analyzed through triangulation techniques and a SWOT matrix. The findings reveal that domestic tourists experienced a meaningful enhancement of cultural understanding after attending the parade, particularly due to the multilingual explanations delivered by the master of ceremonies representing each banjar and the dissemination of cultural content through social media platforms. The ogoh-ogoh tradition embodies spiritual, cultural, and social values, serving as an authentic representation of Balinese culture. Nevertheless, educational gaps remain evident due to the absence of a structured cultural interpretation program, limited regional government budget allocations that resulted in the cancellation of the department-level festival in 2026, and the underutilized role of pecalang officers as cultural information providers. In addition, psychological barriers stemming from religious differences constrain the participation and engagement of non-Hindu domestic tourists. Cross-stakeholder collaboration among traditional villages, government institutions, and tourism industry actors is essential for transforming the ogoh-ogoh event into a cultural tourism platform that is not only visually attractive but also educationally impactful and sustainably transformative. Keywords: Ogoh-Ogoh, Cultural Event, Domestic Tourists, Cultural Education, Balinese Cultural Tourism.